2015
DOI: 10.1093/aob/mcv084
|View full text |Cite
|
Sign up to set email alerts
|

Continent-wide distribution in mycorrhizal fungi: implications for the biogeography of specialized orchids

Abstract: The use of a widespread fungal OTU in P. deformis enables a broad distribution despite high mycorrhizal specificity. The Sebacina OTUs that are used by a range of Australian orchids occur on both sides of the continent, demonstrating that the short-range endemism prevalent in the orchids is not driven by fungal species with narrow distributions. Alternatively, a combination of specific edaphic requirements and a high incidence of pollination by sexual deception may explain biogeographic patterns in southern Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 70 publications
2
41
0
Order By: Relevance
“…Further, Davis et al . () demonstrated that some of the fungi found associating with south‐western Australian orchids are also present in south‐eastern Australia, despite being separated by the arid Nullarbor Plain. As such, there is no evidence that the absence of suitable mycorrhizal fungi constrains the overall geographical range of orchid species associating with Sebacina in south‐western Australia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, Davis et al . () demonstrated that some of the fungi found associating with south‐western Australian orchids are also present in south‐eastern Australia, despite being separated by the arid Nullarbor Plain. As such, there is no evidence that the absence of suitable mycorrhizal fungi constrains the overall geographical range of orchid species associating with Sebacina in south‐western Australia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the closely related monotypic Pheladenia D.L.Jones & M.A.Clem. associates almost entirely with a single OTU of Sebacina across its broad geographical range (Davis et al, 2015). When taken together with the extensive sharing of fungal OTUs between Caladenia spp., these lines of evidence suggest that changes in mycorrhizal specificity is unlikely to have been the main driving mechanism in the diversification of some subgenera of Caladenia.…”
Section: Phylogenetic Patterns Of Host Breadth: Specificitymentioning
confidence: 97%
See 2 more Smart Citations
“…For example, orchids rely on mycorrhizal fungi for nutrients, especially as seedlings (Rasmussen & Rasmussen, 2009). The degree of specialization in these orchid-mycorrhizae relationships varies, with implications for orchid distributions and rarity (Davis, Phillips, Wright, Linde, & Dixon, 2015;Jacquemyn, Brys, Waud, Busschaert, & Lievens, 2015). In turn, the distributions of mycorrhizal fungi depend largely upon edaphic conditions such as soil moisture, pH, nutrients, and organic content (McCormick & Jacquemyn, 2014;Nurfadilah, Swarts, Dixon, Lambers, & Merritt, 2013).…”
Section: Introductionmentioning
confidence: 99%